Spatial heterogeneity in non-parametric efficiency: An application to Italian hospitals. (October 2019) - Auteri, M.; Guccio, C.; Pammolli, F.; Pignataro, G.; Vidoli, F.
Abstract: This paper introduces a new empirical procedure for the estimation of hospitals' technical efficiency in presence of spatial heterogeneity. We propose a methodology that allows treating spatial heterogeneity independently of a predetermined reference to administrative borders. We define geographical spatial regimes, characterised by spatial proximity and homogeneity of relevant demand characteristics, within which to assess the efficiency of hospitals. The methodology has then been tested on a large sample of Italian hospitals, for which their production efficiency has been assessed within homogeneous demand areas. Highlights: We use novel approach to assess technical efficiency accounting for spatial heterogeneity. Spatial heterogeneity is treated by using spatial regimes. Identified spatial regimes are characterised by spatial proximity and homogeneity of demand characteristics. We test the proposed approach on a large sample of Italian hospitals.